Protein preparation, crystallization and preliminary X-ray analysis of Polygonum cuspidatum bifunctional chalcone synthase/benzalacetone synthase - Lu, Heshu (International Union of Crystallography, 2013)
The chalcone synthase (CHS) superfamily of type III polyketide synthases (PKSs) generate the backbones of a variety of plant secondary metabolites. An active bifunctional chalcone synthase/benzalacetone synthase (CHS/BAS) from Polygonum cuspidatum was overexpressed in Escherichia coli as a C-terminally polyhistidine-tagged fusion protein, purified to homogeneity and crystallized using polyethylene glycol 4000 as a precipitant. The production of well shaped crystals of the complex between PcPKS1 and benzalacetone was dependent on the presence of sorbitol and barium chloride as additives. The crystals belonged to the orthorhombic space group P2(1)2(1)2(1), with unit-cell parameters a = 80.23, b = 81.01, c = 122.89 Å, and diffracted X-rays to at least 2.0 Å resolution.